Precedent phenomena of the contemporary russian and spanish mass media as cognitive structures of a linguistic identity - Moiseenko, Lilia V.; Mikheeva, Natalia F. (Universidade Estadual Paulista, 2021)
The present study is important since precedent phenomena, transmitting both traditional and newly created cultural values, are more widely represented in the mass media language. The paper suggests a cognitive approach aimed at identifying the role of knowledge (linguistic, non-linguistic, individual) in forming the precedent unit meaning, being the primary object of research in cognitive science. Examples of universal precedent names (Napoleon, Cinderella, Don Quixote, Adam) suggest that they store culturally valued (thematized) and implicit knowledge shared by communicants. Studying the binary structures (designator/designatum) of a concept defines the development dynamics of the precedent name’s meaning, relevant changes in structure of the core components of meaning, desemantization of the precedent name. Different Russian and Spanish interpretations show that prevailing content varies, and the language meaning of an invariant of universal precedent names reflects not the reality as such but the cognitive structures of a linguistic identity of a particular society.